2013
DOI: 10.1002/ejoc.201301378
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomerism in 3,4,5‐Tri‐(2‐methoxyphenyl)‐2,6‐lutidine

Abstract: Suzuki reaction of tribromo‐2,6‐lutidine with (2‐methoxyphenyl)boronic acid gave 3,4,5‐tris(2‐methoxyphenyl)‐2,6‐lutidine in the form of a mixture of three atropisomers that were stable at room temperature. Each isomer was isolated and fully characterized, including by X‐ray structure determination. One of the isomers, being a racemic mixture, was separated into individual enantiomers by using semipreparative chiral HPLC. Their absolute stereochemistry was initially assigned on the basis of computational calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Our previous results 29 as well as data collected in Table 1 (entries 4, 6, 9, 10) indicated that some catalytic systems with a properly chosen base could be suitable for regioselective diarylation of 8 and 9. In a subsequent study we decided to apply ready to use ferrocenylphosphine-based catalyst Pd(dppf)Cl 2 ×CH 2 Cl 2 , mainly because of its air stability and high activity.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…Our previous results 29 as well as data collected in Table 1 (entries 4, 6, 9, 10) indicated that some catalytic systems with a properly chosen base could be suitable for regioselective diarylation of 8 and 9. In a subsequent study we decided to apply ready to use ferrocenylphosphine-based catalyst Pd(dppf)Cl 2 ×CH 2 Cl 2 , mainly because of its air stability and high activity.…”
Section: Resultsmentioning
confidence: 72%
“…In a recent paper we demonstrated that Buchwald ligand S-Phos in connection with palladium donor Pd(OAc) 2 in the presence of K 3 PO 4 allows Suzuki cross-coupling of pyridine 3 with 2-methoxyphenylboronic acid in less than an hour. 29 During an optimization study, this catalytic system proved superior to others, e. g.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations